The use of peak flow meters in acute asthma in the emergency department - Parris, Panayotes (My University, 2016)
Objectives: This study aimed to survey and compare the use of the Peak Flow Meter (PFM) with respect to asthma exacerbations in the Emergency Department (ED) by healthcare practitioners from both the private and public sectors attending the Emergency Medicine Society of South Africa symposium. Design: A questionnaire-based cross-sectional study Setting: Emergency Medicine Society of South Africa 2012 Symposium in Johannesburg. Participants: Medical doctors and nursing staff from various EDs attending the symposium. Method: Prospective questionnaire-based study. Main Results: The majority of the delegates (79%) believed in the role of the PFM, but only 61.7% used it. Forty six percent of participants using the PFM were proficient with its use, with only a quarter knowing how to correctly compare the readings to a nomogram. There were perceived equipment shortages that may also have limited the use of the PFM in the ED. Conclusions: The ED is a unique enviroment in which the use of a PFM mandated by the current asthma exacerbation guidelines has not been proven to be applicable. The PFM has never been shown to be of benefit to either adult or paediatric patient outcome in the ED management of acute asthma exacerbations. In this survey of healthcare practioners (HCP) in Johannesburg, the PFM was found to be an under utilised tool in the management of acute asthma exacerbations. In light of this it is recommended that these guidelines together with the use of the PFM be reviewed by the SEPs who are managing the acute asthma exacerbations in the ED.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Medicine in Emergency Medicine. Johannesburg, 2014